Memory complaints are associated with impaired working memory and reduced frontal cortical thickness in mid‐life surgically menopausal women: Neuropsychology/Early detection of cognitive decline with neuropsychological tests. (7th December 2020) - Reuben, Rebekah B.; Almey, Anne; Gervais, Nicole J.; Au, April; Duchesne, Annie; Gravelsins, Laura; Brown, Alana; Kannampuzha, Courtney; Perovic, Mateja; Bernardini, Marcus; Eisen, Andrea; Meschino, Wendy; et al.
Abstract: Background: Alzheimer's disease (AD)‐related brain pathology is observed in participants within the normal ranges of cognitive assessments (Delacourte et al., 1999). Consequently, there is increased interest in subjective cognitive decline (SCD), a self‐experienced decline in cognition, as an early risk factor (Jessen et al., 2014). SCD is associated with earlier conversion to mild cognitive impairment (MCI) and AD (Jessen et al., 2010; Reisberg et al., 2010), poorer performance on cognitive tasks, and cortical thinning in AD‐related regions (Schultz et al., 2015; Sánchez‐Benavides et al., 2018). Women with surgical menopause prior to age 50 have an increased risk of AD (Rocca et al., 2007). Women with bilateral salpingo‐oophorectomy (BSO) without estradiol (E2) therapy in mid‐life show decreases in WM performance and volumetric declines in the frontal cortex and hippocampus compared to controls (Almey et al., 2018; Gervais et al., 2018). Method: The current study evaluated the association of memory complaints with WM performance and frontal cortical thickness in a mid‐life cohort of at‐risk women with BSO. Participants with memory complaints (n = 42) and without (n = 30) completed demographics and neuropsychological tasks to assess WM. A subset of these participants with memory complaints (n = 11) and without (n = 14) were scanned using a 3T Siemens scanner, and cortical thickness was obtained from T1‐weighted scans using CIVET 2.1.1 (Ad‐Dab'bagh et al., 2005). Analyses were performed using R 1.1.4 (R Core Team, 2018). Result: Our analyses revealed participants with memory complaints performed significantly worse on WM tasks than those without. Furthermore, we found participants with memory complaints had significantly thinner cortices within the left ventrolateral prefrontal cortex (vlPFC), a region associated with WM (Badre & Wagner, 2007). Conclusion: Our preliminary results demonstrate memory complaints are associated with impaired WM performance and frontal cortical thinning in women with BSO. The results suggest that women with surgical menopause and memory complaints show differences associated with SCD in WM function and frontal cortical structure at an early age (Wang et al., 2004). Ongoing research is evaluating effects of memory complaints on cognition and brain structure within spontaneously menopausal women in the COMPASS‐ND database (CCNA, 2020).